(untitled) (Web of Teachers: Inderscience Research, 2024)
This article explores the effectiveness of collaborative learning over traditional teaching methods in enhancing student engagement and comprehension, particularly in theoretical subjects like Comparative Typology. Through an experimental design, typology seminars were conducted using both traditional and collaborative learning approaches, allowing for a comparative analysis of student outcomes, participation levels, and understanding of course material. Data from the experiment indicate that collaborative learning not only improves academic performance but also fosters a deeper grasp of complex concepts, encouraging critical thinking and peer interaction. These findings suggest that collaborative learning can be a valuable alternative to traditional methodologies in teaching theoretical sciences.